Gustav Shpet, Immanuel Kant and Terminist Logic - Maryse Dennes (Кантовский сборник)
In his book Appearance and Sense Gustav Shpet, comparing Immanuel Kant’s transcendental logic with the traditional probleтs of the philosophy of language, thought it appropriate and conceptually effective to turn to the medieval scholastic debate on universals. Later, in the Hermeneutics and Its Problems, he goes back to this discussion and notes that it was the framework in which the thirteenth-century tradition of “terminist” logic was formed. Shpet attributed the fruitfulness of this approach to his concept of the inner form of the word. Terminist logic is based on the definition and analysis of such terms as significatio, suppositio, expositio, exponibilia, and Shpet, in examining them, demonstrates the consonance of his concept with terminist logic. Proceeding from thirteenth-century logical studies, he proposes his own approach to resolving the contradictions found in Kant’s critical philosophy. Shpet believed that transcendental idealism failed to resolve the problem of the relation between intuition and concept (even though Kantian “schematism” was a search for such resolution). This inherent Kantian problem is for Shpet a take-off point to which he kept returning throughout his career. I will pay particular attention to such works as Appearance and Sense, in which Shpet broadens the problematics of Husserl’s phenomenology, and The Inner Form of the Word, in which he reinterprets Humboldt’s philosophy of language. In both cases Shpet shows that neither Husserl nor Humboldt managed to overcome the Kantian contradiction. So the reference to Kant is a starting point from which Shpet proceeds to put forward and consolidate his hypotheses. It is in thirteenth-century terminist logic that Shpet will see an original way of overcoming the Kantian contradiction and direct us toward interpreting the problems of the philosophy of language.